Nostril Morphometry Evaluation before and after Cleft Lip Surgical Correction: Clinical Evidence - Feijo, Mario Jorge Frassy; Brandão, Stella Ramos; Pereira, Rui Manoel Rodrigues; Santos, Mariana Batista de Souza; Justino da Silva, Hilton (International Archives of Otorhinolaryngology, 2014)
Introduction The purpose to this work is to review systematically the morphological changes of the nostrils of patients undergoing surgery for correction of cleft lip and identify in the literature the issues involved in the evaluation of surgical results in this population.Review of Literature A review was conducted, searching for clinical evidence from MEDLINE. The search occurred in January 2012. Selection criteria included original articles and research articles on individual subjects with cleft lip or cleft palate with unilateral nostril anthropometric measurements before and after surgical correction of cleft lip and measurements of soft tissues. There were 1,343 articles from the search descriptors and free terms. Of these, five articles were selected.Discussion Most studies in this review evaluated children in Eastern countries, using different measurement techniques but with the aid of computers, and showed improved nostril asymmetry postoperatively compared with preoperatively.Conclusion There is a reduction of the total nasal width postoperatively compared with preoperative measurements in patients with cleft lip.
Keywords: cleft lip; anthropometry; nose